2005
DOI: 10.1158/1055-9965.epi-05-0191
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of an Intervention to Increase Fruit and Vegetable Intake in Curatively Treated Patients with Early-Stage Head and Neck Cancer

Abstract: The leading cause of death in patients who have had curatively treated early-stage head and neck cancer is a second primary cancer of the upper aerodigestive tract (lung, esophagus, larynx, pharynx, and oral cavity cancers). Low fruit and vegetable intake has been associated with increased risk of primary head and neck cancer and the available data suggest that increasing intake following diagnosis may reduce the risk of a second primary cancer. The goal of this study was to develop and test an easily administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…The study has been described in detail elsewhere 44. Briefly, the study goal was to increase fruit and vegetable consumption in patients with early-stage, curatively treated head and neck cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The study has been described in detail elsewhere 44. Briefly, the study goal was to increase fruit and vegetable consumption in patients with early-stage, curatively treated head and neck cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies were directed at breast cancer survivors, but colorectal and prostate cancer survivors were also studied. Of the 34 studies, 14 were aimed at increasing exercise or physical activity (Basen‐Engquist et al., ; Bennett, Lyons, Winters‐Stone, Nail, & Scherer, ; Courneya et al., ; Fillion et al., ; Hatchett, Hallam, & Ford, ; Jones, Courneya, Fairey, & Mackey, ; Jones et al., ; Matthews et al., ; Mutrie et al., ; Pinto, Frierson, Rabin, Trunzo, & Marcus, ; Pinto, Papandonatos, Goldstein, Marcus, & Farrell, ; Pinto et al., ; Rogers et al., ; Vallance, Courneya, Plotnikoff, & Mackey, ), six at enhancing diet quality (Cartmel, Bowen, Ross, Johnson, & Mayne, ; Chlebowski et al., ; Djuric et al., ; Hebert et al., ; Pierce et al., , ), and nine at changing both exercise and diet behaviour (Campbell et al., ; Christy et al., ; Demark‐Wahnefried et al., , , ; Harris et al., ; Morey et al., ; Mosher et al., ; Ottenbacher et al., ). Furthermore, four studies were aimed at ceasing smoking (Cox et al., ; Emmons et al., ; Schnoll et al., ; Wakefield, Olver, Whitford, & Rosenfeld, ) and one at reducing both alcohol intake and tobacco use (Duffy et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…For participants in the preparation stage, the intervention focused on the skills and strategies necessary to change behaviour. The change in self‐reported intake of fruit and vegetables was significantly greater in the intervention group compared to the usual care control group (Cartmel et al., ). Not only studies applying usual care in the control group, but also studies with a non‐tailored intervention for the control group showed their efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upper aerodigestive tract is the major area affected with the second primaries of lung cancer, esophageal cancer, pharyngeal, laryngeal, and oral cancers. 12 Thus, a precautionary approach before the advance of invasive cancer or progress of second primary tumors is highly desirable.…”
Section: Stages Of Development and Precancerous Formsmentioning
confidence: 99%